2005
DOI: 10.1039/b500044k
|View full text |Cite
|
Sign up to set email alerts
|

Spectral resolution of fluxional organometallics. The observation and FTIR characterization of all-terminal [Rh4(CO)12]

Abstract: In situ FTIR spectroscopy at 1 cm(-1) resolution was conducted on n-hexane solutions of the bridged [Rh4(CO)9(mu-CO)3] in the interval T= 268-288 K and P(T)= 0.1-7.0 MPa using either helium or carbon monoxide as dissolved gas. Analysis of the spectral data sets was conducted using band-target entropy minimization (BTEM), in order to recover the pure component spectra. A new spectral pattern was recovered with terminal vibrations at 2075, 2069.8, 2044.6 and 2042 cm(-1). The new spectrum is consistent with an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 64 publications
4
24
0
Order By: Relevance
“…2023 cm À1 was reconstructed during the reaction of TMA with Rh 2 (CO) 4 Cl 2 . The two BTEM estimates are not consistent with the impurities Fe(CO) 5 , Ni(CO) 4 , and Mo(CO) 6 which have sometimes been detected in our other in-situ spectroscopic studies [21]. Due to the low concentrations of these two minor species, their FIR and low wavenumber MIR spectra could not be obtained and therefore their identification is not presently possible.…”
Section: Discussionmentioning
confidence: 87%
“…2023 cm À1 was reconstructed during the reaction of TMA with Rh 2 (CO) 4 Cl 2 . The two BTEM estimates are not consistent with the impurities Fe(CO) 5 , Ni(CO) 4 , and Mo(CO) 6 which have sometimes been detected in our other in-situ spectroscopic studies [21]. Due to the low concentrations of these two minor species, their FIR and low wavenumber MIR spectra could not be obtained and therefore their identification is not presently possible.…”
Section: Discussionmentioning
confidence: 87%
“…In solution, fluxionality of all COs was observed, and this leads to numerous experimental and theoretical studies. The long sought all-terminal variety of Rh 4 (CO) 12 was not identified until after the advent of the latest generation of signal processing techniques [55]. The dinuclear Rh 2 (CO) 8 is also non-isolatable and was first observed under hundreds of bar CO partial pressure [56].…”
Section: Homometallic Casementioning
confidence: 98%
“…[26][27][28] This algorithm is based on a spectral entropy minimization objective and was proven to be an efficacious numerical tool that is able to elucidate the pure component spectral profiles of unknown chemical species with minute spectral signal contributions. 33,38,40 Comparison studies have demonstrated BTEM to be generally superior in resolving pure component spectra from multi-component systems with highly overlapping FT-IR bands. 26,28 One notable application of the BTEM algorithm was the successful elucidation of the long sought after rhodium tetracarbonyl hydride HRh(CO) 4 spectrum, 33 which is the first spectroscopic proof of its existence under hydroformylation conditions of reaction temperature T ¼ 285-303 K, partial pressures P H2 ¼ 1.0-5.0 MPa, P CO ¼ 1.0-5.0 MPa, and initial moles of catalyst precursor § [Rh 4 (CO) 12 ] ¼ 58-315 mg in n-hexane solvent.…”
Section: Multivariate Calibration For Unknown Chemical Species Absorpmentioning
confidence: 99%